The Influence Of Taste And Menu Diversity On Customer Loyalty At Caffe Hitado Bandar Lampung - Jonathan Mikhael Siregar; Syahril Daud (Cita konsultindo, 2024)
The aim of this research is to find out the influence of taste and menu diversity on customer loyalty for consumers of Caffe Hitado Bandar Lampung. The sample for this research is 100 respondents calculated using the Cochran formula. This research uses quantitative methods using IBM SPSS 25. Based on the research results, it is known that taste has a positive and significant effect on customer loyalty. Then, menu diversity has a positive and significant effect on customer loyalty. Furthermore, the taste and diversity of the menu together have a positive and significant effect on customer loyalty. It is hoped that this research can help Caffe Hitado Bandar Lampung in increasing and maintaining customer loyalty while maintaining the quality of its taste and adding menu variants so that consumers feel satisfied and interested in coming back.